Evaluation of treatment results and access to health support of malignant pleural mesothelioma patients in Cappadocia (Annals of Medical Research, 2021)
Aim: Malignant Pleural Mesothelioma (MPM) is frequently observed due to erionite in Cappadocia. In this study, patients who live in Cappadocia region and were treated in Nevsehir State Hospital were evaluated.Material Method: In this study, the data of 22 patients admitted to Nevşehir State Hospital and diagnosed with MPM between 15.7.2009-27.08.19 were evaluated retrospectively. The patients' overall survival (OS), progression-free survival (PFS) and access to health support were examined.Results: The median follow-up period was 26 (range 1-153) months. The median age of the patients at the time of diagnosis was 65 years (range 36-86). Only 2 (9.1%) patients were localized / operable at the time of diagnosis; three patients (13.6%) were metastatic and 17 (77.3%) were in-operable. The female / male ratio of our patients was 1/1. The 3 patients (13.6%) were diagnosed at Nevşehir State Hospital, and 19 patients (86.4%) were diagnosed outside the Cappadocia. During the follow-up period, 19 patients (86.4%) deceased and 3 patients (13.6%) were alive. The median OS of the patients was 19 (range 1-133) months. The relapse was observed in 19 patients (86.4%). The median PFS value is 10 (range 1-126) months.Conclusion: There is not enough infrastructure in Cappadocia in terms of diagnosis and treatment of MPM. The people of Cappadocia need to be supported in terms of access to MPM treatment. The OS of MPM has not improved significantly over the past 40 years.